DEA WINDOW ANALYSIS OF INDONESIAN ISLAMIC BANK EFFICIENCY - Aam Slamet Rusydiana; Aisyah As-Salafiyah (Journal of Islamic Monetary Economics and Finance, 2021)
This study measures the efficiency of Islamic banks in Indonesia using data envelopment analysis (DEA) window methods on 14 Indonesian Islamic banks covering the period from 2011 to 2020. The results show that the efficiency of Islamic banks averages 80% and showed an increasing trend over the study period. Based on stability measures, namely standard deviation (SD), Long Distance per Window (LDW), Long Distance per Period (LDP), and Long Distance per Year (LDY), we find that the efficiency of PT Bank BRI Syariah (BSI) and PT Bank Syariah Mandiri (BSI) is relatively stable.